Meclizine Prevents Ovariectomy-Induced Bone Loss and Inhibits Osteoclastogenesis Partially by Upregulating PXR - Guo, Jiachao; Li, Weijin; Wu, Yingxing; Jing, Xingzhi; Huang, Junming; Zhang, Jiaming; Xiang, Wei; Ren, Ranyue; Lv, Zhengtao; Xiao, Jun; Guo, Fengjing (Frontiers in Pharmacology, 2017)
Pregnane X receptor (PXR) which belongs to the nuclear hormone receptor superfamily plays vital roles in several biological functions, especially in the inflammatory procedure. Besides that, PXR is revealed by recent studies to have essential effects on bone tissue. As an agonist of PXR, meclizine is a piperazine-derived histamine H1 antagonist, and has been frequently used for prevention and treatment of vomiting and nausea. Because osteoclastogenesis is characterized by the activation of inflammation-related signaling pathways, we speculated that meclizine may affect formation and function of osteoclast. In the present study, we explored the effect of meclizine on RANKL-induced osteoclastogenesis both in vivo and in vitro. In primary bone marrow-derived macrophages (BMMs), meclizine reduced osteoclast formation and bone resorption in a dose-dependent manner, while knockdown of PXR with siRNA partially abrogated the osteoclastogenesis inhibition of meclizine. On the one hand, at the molecular level, meclizine attenuated RANKL-induced activation of c-Fos, NFATc1, nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPKs), including ERK and p38, but not JNK. Meanwhile, meclizine reduced the expression of osteoclast-specific genes, including TRAP, MMP9, Cathepsin K and NFATc1. On the other hand, meclizine decreased OVX-induced bone loss by repressing osteoclast activity. In conclusion, our results indicated that meclizine inhibits osteoclastogenesis via regulation of several RANKL signaling pathways and PXR was involved in the processes. Therefore, meclizine may be considered as a novel therapeutic candidate for osteoclast-related diseases.